Preparation method and application of polymer-coated sulfide composite solid electrolyte
Through 3D pulse printing technology, polymer and sulfide are combined on the electrode surface to form a composite solid electrolyte with polymer coated sulfide, which solves the problem of decreased conductivity and insufficient cycle stability of sulfide solid electrolyte after film formation, achieves high ionic conductivity and stability, and improves the energy density of solid battery.
Patent Information
- Application Number
- CN202311568041.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-22
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-11-22
AI Technical Summary
The existing sulfide solid electrolyte has problems such as the decrease in conductivity of the electrically reduced, poor compatibility with the positive and negative electrodes after film formation, and insufficient cycle stability.
3D pulse printing technology is used to recombinate polymer and sulfide in situ on the electrode surface to form a composite solid electrolyte with polymer-coated sulfide, which increases the contact area between the electrolyte and the electrode, reduces interface resistance and suppresses interface side reactions.
It improves the ionic conductivity and cycling stability of solid-state batteries, reduces the battery volume, and improves the volume energy density of all-solid-state batteries.
Smart Images

Figure CN117497832B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials, and particularly relates to a preparation method and application of a composite solid electrolyte of polymer-coated sulfide. Background Art
[0002] All-solid-state batteries have attracted widespread attention due to their high safety, high energy density and stable cycle efficiency. Sulfide solid electrolytes have high ionic conductivity, but there are still problems such as decreased conductivity after film formation, poor compatibility with positive and negative electrodes, and insufficient cycle stability.
[0003] In order to solve the problem of unstable positive electrode interface, a lot of research work has introduced positive electrode coating to improve the above problems. However, these solutions also have problems such as thick coating layer (>10μm) and high cost, which also affects the positive electrode potential.
[0004] At the same time, the existing technology also has the problem of negative electrode instability. In order to solve the problem of sulfide instability on the negative electrode, the existing technology mainly uses lithium-containing alloys to increase the negative electrode potential, thereby inhibiting the growth of lithium dendrites. However, the increased negative electrode potential also reduces the energy density of the battery to a certain extent. In addition, there is also technology that uses graphite negative electrodes, but its specific capacity is much lower than that of metals (350mAh·g -1 <3870mAh·g -1 ), which is also not conducive to improving the energy density of solid-state batteries.
[0005] In summary, there is an urgent need to provide an electrolyte that is beneficial to improving ionic conductivity and cycle stability. Summary of the invention
[0006] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a preparation method and application of a composite solid electrolyte of polymer-coated sulfide. The composite solid electrolyte prepared by the preparation method of the present invention is applied in a solid-state battery, which is beneficial to improving ionic conductivity and cycle stability.
[0007] A first aspect of the present invention provides a method for preparing a polymer-coated sulfide composite solid electrolyte.
[0008] Specifically, the preparation method of the polymer-coated sulfide composite solid electrolyte comprises the following steps:
[0009] Passing the polymer solution into a liquid nozzle of a 3D printing device;
[0010] Passing sulfide into a powder nozzle of a 3D printing device;
[0011] Spraying the polymer solution onto the electrode through a liquid nozzle of a 3D printing device to form a grid-shaped polymer film;
[0012] Dispersing the sulfide into the gaps of the polymer film through a powder nozzle of a 3D printing device;
[0013] The polymer film and the sulfide are printed layer by layer in a pulse printing manner;
[0014] Rolling is performed to obtain the composite solid electrolyte (the composite solid electrolyte is connected with the electrode).
[0015] Preferably, spraying the polymer solution onto the electrode through a liquid nozzle of a 3D printing device specifically includes:
[0016] The polymer solution is sprayed onto the positive electrode and / or the negative electrode through a liquid spray head.
[0017] Preferably, the rolling process includes: rolling the electrode, the polymer and the sulfide layer together; or, sandwiching the polymer and the sulfide layer between the positive electrode and the negative electrode for rolling.
[0018] Preferably, the rolling process conditions are: rolling at 5-300 MPa, more preferably 30-70 MPa, for example, rolling at 5 MPa, 10 MPa, 20 MPa, 30 MPa, 50 MPa, 60 MPa. This ensures the density of the polymer-coated sulfide composite solid electrolyte and reduces the equipment requirements and costs.
[0019] Preferably, the rolling speed is 10-80 cm / min, more preferably 30-60 cm / min, to ensure the density of the solid electrolyte.
[0020] Preferably, the sulfide is selected from Li 3 PS 4 , Li 4 P 2 S 6 or Li 7-a PS 6-a X a , wherein X is at least one of Cl, Br, and I, and the value of a is 0.5 to 2.
[0021] Preferably, the polymer in the polymer solution is at least one selected from polytetrafluoroethylene (PTFE), polyethylene oxide, polyethylene, polypropylene, polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), and polyethylene oxide (PEO).
[0022] Preferably, the polymer solution can be replaced by succinonitrile (SN).
[0023] Preferably, the polymer solution is mixed with the lithium salt before passing the polymer solution into the liquid nozzle of the 3D printing device.
[0024] Preferably, the lithium salt includes LiTFSI (lithium bis(trifluoromethanesulfonyl)imide).
[0025] Preferably, in the polymer solution, the molar ratio of the polymer to the lithium salt is (20-40):1, more preferably (25-30):1.
[0026] Preferably, the mass concentration of the polymer solution is 0.5-1.5 g / cm 3 .
[0027] Preferably, the solvent in the polymer solution is at least one selected from acetone, N-methylpyrrolidone and toluene.
[0028] Preferably, during the process of spraying the polymer solution onto the electrode through the liquid nozzle of the 3D printing device, the solvent contained in the polymer solution is removed by a dryer placed between the liquid nozzle and the electrode.
[0029] Preferably, the sulfide is in powder form.
[0030] A second aspect of the present invention provides a composite solid electrolyte of a polymer-coated sulfide.
[0031] Specifically, the polymer-coated sulfide composite solid electrolyte is prepared by the above preparation method.
[0032] Preferably, the mass of the polymer accounts for 1.5% to 49.5% of the total weight of the composite solid electrolyte, more preferably 2% to 49%, for example 2%, 10%, 20%, 30%, 40%, 49%.
[0033] Preferably, the mass of the sulfide accounts for 50-98% of the total weight of the composite solid electrolyte, and more preferably 90-96%.
[0034] Preferably, the mass of the lithium salt accounts for 0.001-5% of the total weight of the composite solid electrolyte, and more preferably 0.005-3%.
[0035] Preferably, the polymer-coated sulfide composite solid electrolyte has a dense structure.
[0036] Preferably, the composite solid electrolyte is in the form of a thin film.
[0037] Preferably, the thickness of the composite solid electrolyte is 0.05 to 3 mm, more preferably 0.1 to 2.8 mm.
[0038] The third aspect of the present invention provides the use of a composite solid electrolyte of polymer-coated sulfide.
[0039] A lithium ion battery comprises the composite solid electrolyte of polymer-coated sulfide.
[0040] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0041] The solid electrolyte of the present invention is to composite polymers and sulfides on the electrode surface by 3D pulse printing, reduce the interface resistance and mechanical degradation during the charge and discharge process, thereby improving the battery cycle stability. There are three main problems between the sulfide and the high-voltage oxide positive electrode interface: chemical and electrochemical side reactions at the interface, the volume change of the active substance during the charge and discharge cycle leads to the formation of interface holes, and the conductive carbon in the positive electrode accelerates the decomposition of the sulfide electrolyte. On the negative electrode side, the interface between the sulfide and metallic lithium mainly has three problems: lithium dendrite growth, interface side reactions, and interface contact deterioration during the cycle. In order to solve the interface problem between the sulfide electrolyte and the positive and negative electrodes, the present invention uses a 3D pulse printing method to in-situ composite polymers and sulfides on the electrode, which increases the contact area between the sulfide solid electrolyte and the electrode and reduces the interface resistance. At the same time, the presence of an appropriate amount of polymer also inhibits the interface side reaction to a certain extent. The solid electrolyte of the present invention improves the contact effect and interface stability between the electrolyte and the electrode, inhibits the mechanical degradation of the composite electrode and the formation of lithium dendrites during the battery cycle, thereby improving the battery cycle stability. On the other hand, the present invention can also reduce the volume of the sulfide solid-state battery, thereby further improving the volume energy density of the sulfide all-solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 It is a schematic diagram of the mechanism structure of 3D pulse printing of the present invention. DETAILED DESCRIPTION
[0043] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0044] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0045] Existing sulfide solid electrolytes are very likely to undergo side reactions with positive and negative electrode materials, and the side reaction products will affect the interface connection and grow lithium dendrites on the lithium metal negative electrode, causing a short circuit.
[0046] Based on this, an embodiment of the present invention provides a composite solid electrolyte of polymer-coated sulfide that is stable to positive and negative electrodes, which includes: sulfide and a strategy for maintaining electrode interface stability, and the strategy for maintaining electrode interface stability is implemented by a method of 3D pulse printing polymer-coated sulfide.
[0047] The embodiment provides a polymer-coated sulfide solid electrolyte that is stable to the positive and negative electrodes. The polymer and sulfide are composited on the electrode surface by 3D pulse printing, which reduces the interface resistance and mechanical degradation during the charge and discharge process, thereby improving the battery cycle stability. There are three main problems at the interface between sulfide and high-voltage oxide positive electrode: chemical and electrochemical side reactions at the interface, the volume change of active substances during the charge and discharge cycle leads to the formation of interface holes, and the conductive carbon in the positive electrode accelerates the decomposition of the sulfide electrolyte. On the negative electrode side, the interface between sulfide and metallic lithium mainly has three problems: lithium dendrite growth, interface side reactions, and deterioration of interface contact during the cycle. In order to solve the interface problem between the sulfide electrolyte and the positive and negative electrodes, the embodiment uses a 3D pulse printing method to composite polymers and sulfides in situ on the electrode, which increases the contact area between the sulfide solid electrolyte and the electrode and reduces the interface resistance. At the same time, the presence of an appropriate amount of polymer also suppresses the interface side reactions to a certain extent. The prepared polymer-coated sulfide solid electrolyte improves the contact effect and interface stability between the electrolyte and the electrode, inhibits the mechanical degradation of the composite electrode and the formation of lithium dendrites during the battery cycle, thereby improving the battery cycle stability. On the other hand, this embodiment can also reduce the volume of the sulfide solid-state battery, thereby further improving the volume energy density of the sulfide all-solid-state battery.
[0048] In one embodiment, the sulfide is Li 3 PS 4 , Li 4 P 2 S 6 or Li 7 -aPS 6 -aY a , wherein Y is at least one of Cl, Br, and I, and the value of a is 0.5 to 2.
[0049] In one embodiment, the mass of the polymer accounts for 2% to 49% of the total weight of the composite solid electrolyte.
[0050] In one embodiment, the composite solid electrolyte is a dense structure.
[0051] In one embodiment, the polymer-coated sulfide composite solid electrolyte is in the form of a thin film, and the thickness of the film is 0.05 to 3 mm.
[0052] A method for preparing a polymer-coated sulfide solid electrolyte, comprising the following steps:
[0053] Dissolving the polymer and lithium salt in a suitable solvent to obtain a polymer solution, and connecting it to a 3D printed liquid nozzle;
[0054] Connect the sulfide powder to the 3D printing powder nozzle;
[0055] The polymer solution is sprayed onto the electrode through a liquid nozzle to form a grid-like polymer film, and the small molecule solvent that may be contained in the liquid is removed by a dryer placed between the nozzle and the electrode;
[0056] The sulfide powder is dispersed in the gaps of the polymer film through a powder nozzle;
[0057] The polymer film and sulfide powder are printed layer by layer in a pulse printing method;
[0058] The composite of the polymer and the sulfide sprayed on the electrode is rolled to obtain a solid electrolyte of the polymer-coated sulfide connected to the electrode.
[0059] In one embodiment, the polymer solution is sprayed onto the electrode through a liquid spray head, specifically comprising:
[0060] A solution of polyethylene oxide, polyethylene, polypropylene, polyacrylonitrile and polyvinylidene fluoride is sprayed onto at least one of the positive electrode and the negative electrode, and the contained solvent is removed by a dryer under the spray head.
[0061] In one embodiment, the rolling pressure is 5-300 MPa, which ensures the density of the polymer-coated sulfide composite solid electrolyte while reducing equipment requirements and costs.
[0062] In one embodiment, the rolling speed is 10-80 cm / min, which ensures the density of the solid electrolyte.
[0063] Figure 1 The schematic diagram of the mechanism structure of the 3D pulse printing of the present invention is that a polymer grid is first printed on the surface of the positive electrode substrate (the grid is composed of a plurality of small squares, a polymer layer is between every two small squares, and a sulfide layer is inside the small squares), and then a sulfide is printed in each square, and then the polymer layer is printed, the polymer and the sulfide are printed alternately, and after the printing is completed, roller pressing is performed to form a structure of polymer-coated sulfide.
[0064] A lithium ion battery comprises a polymer-coated sulfide solid electrolyte that is stable to positive and negative electrodes according to the present invention.
[0065] The present invention will be further described below through several specific embodiments.
[0066] Example 1: Preparation of composite solid electrolyte
[0067] A PTFE-coated Li 3 PS 4 Composite solid electrolyte PTFE@Li 3PS 4 The preparation method comprises the following steps:
[0068] Weigh LiCoO according to the mass ratio of 8:1:1 2 , PVDF, VGCF (carbon fiber) conductive carbon, NMP (N-methylpyrrolidone) as solvent, mixed and ground for 10 minutes and then coated on aluminum foil. During coating, the active material (LiCoO 2 ) loading is 15 mg / cm 2 Around, a composite positive electrode is obtained;
[0069] With the composite cathode as the substrate, PTFE and LiTFSI are mixed at a molar ratio of 30:1, dissolved in acetone, and a polymer solution is obtained. The solution is sprayed out from the liquid nozzle of the 3D printing device in a mist form and printed. The acetone solvent is removed by a dryer connected under the nozzle. The diameter of the fibrous polymer is controlled to be about 5 μm, and the width of each small square is about 20 μm. A grid-like PTFE layer is obtained. The substrate of the PTFE layer is the composite cathode, and the liquid nozzle stops printing.
[0070] Sulfide Li 3 PS 4 The powder nozzle of the 3D printing device is ejected into the small squares printed on the PTFE layer. The polymer solution is mixed with Li 3 PS 4 The total area of the printed grid is 3×3cm. 2 The gap between each two small squares is 5 μm, and the interval is 5 seconds. Repeat 20 layers to obtain a printed composite. Then, the composite is rolled in a roller press at a speed of 50 cm / min and a pressure of 50 MPa to obtain a polymer-coated sulfide composite solid electrolyte PTFE@Li 3 PS 4 , and the composite solid electrolyte PTFE@Li 3 PS 4 The ionic conductivity is 1.7×10 -3 S / cm.
[0071] Using 20μm Li metal foil as the negative electrode, the all-solid-state battery was assembled by roller pressing at a pressure of 50MPa and the electrochemical performance was tested.
[0072] Comparative Example 1
[0073] Direct in-situ solvent mixing and drying to prepare PTFE / Li 3 PS 4 (Control group) Sulfide solid electrolyte (ie, in Comparative Example 1, pulse printing is not used, but equal amounts of PTFE and Li 3 PS 4, solvent mixed and coated on the surface of the composite positive electrode), using 20μm Li metal foil as the negative electrode, the all-solid-state battery was assembled by roller pressing at a pressure of 50MPa and the electrochemical performance was tested.
[0074] The electrochemical performance test conditions of Example 1 and Comparative Example 1 are: current 0.3C rate, voltage range 3.0~4.3V (vs.Li + / Li), cycled 500 times, and the test comparison results are shown in Table 1.
[0075] Table 1
[0076]
[0077] It can be seen from Table 1 that the ionic conductivity of the composite solid electrolyte prepared by 3D pulse printing in Example 1 is higher than that in Comparative Example 1, and the 100-cycle capacity retention rate is as high as 96%.
[0078] Example 2: Preparation of composite solid electrolyte
[0079] A PVDF-coated Li 4 P 2 S 6 Composite solid electrolyte PVDF@Li 4 P 2 S 6 The preparation method comprises the following steps:
[0080] Weigh LiCoO according to the mass ratio of 8:1:1 2 , PVDF, VGCF (carbon fiber) conductive carbon, NMP (N-methylpyrrolidone) as solvent, mixed and ground for 10 minutes and then coated on aluminum foil. During coating, the active material (LiCoO 2 ) loading is 15 mg / cm 2 Around, a composite positive electrode is obtained;
[0081] With the composite cathode as the substrate, PVDF and LiTFSI are mixed at a molar ratio of 30:1, dissolved in NMP, and a polymer solution is obtained, which is sprayed out from the liquid nozzle of the 3D printing device in a mist form and printed. The NMP solvent is removed by a dryer connected under the nozzle. The diameter of the fibrous polymer is controlled to be about 5 μm, and the width of the grid is about 20 μm, to obtain a grid-like PVDF layer, the substrate of the PVDF layer is the composite cathode, and the liquid nozzle suspends printing;
[0082] Sulfide Li 4 P 2 S 6 The powder spray nozzle of the 3D printing device is ejected into the grid of the PVDF layer, and the polymer solution is mixed with Li 4 P 2 S6 The total area of the printed grid is 3×3cm. 2 After an interval of 5 seconds, the powder nozzle starts printing powder, and the printing is repeated for 20 layers to obtain a printed composite. The composite is then rolled in a roller press at a speed of 50 cm / min and a pressure of 50 MPa to obtain a polymer-coated sulfide composite solid electrolyte PVDF@Li 4 P 2 S 6 , and the composite solid electrolyte PVDF@Li 4 P 2 S 6 The ionic conductivity is 2.1×10 -3 S / cm.
[0083] Using 20μm Li metal foil as the negative electrode, the all-solid-state battery was assembled by roller pressing at a pressure of 50MPa and the electrochemical performance was tested.
[0084] Comparative Example 2
[0085] Direct in-situ solvent mixing and drying to prepare PVDF / Li 4 P 2 S 6 (Control group) Sulfide solid electrolyte (ie, in Comparative Example 2, pulse printing is not used, but equal amounts of PVDF and Li 4 P 2 S 6 , solvent mixed and coated on the surface of the composite positive electrode), using 20μm Li metal foil as the negative electrode, the all-solid-state battery was assembled by roller pressing at a pressure of 50MPa and the electrochemical performance was tested.
[0086] The electrochemical performance test conditions of Example 2 and Comparative Example 2 are: current 0.3C rate, voltage range 3.0~4.3V (vs.Li + / Li), cycled 500 times, and the test comparison results are shown in Table 2.
[0087] Table 2
[0088]
[0089]
[0090] It can be seen from Table 2 that the ionic conductivity of the composite solid electrolyte prepared by 3D pulse printing in Example 2 is higher than that in Comparative Example 2, and the 100-cycle capacity retention rate is as high as 97%.
[0091] Example 3: Preparation of composite solid electrolyte
[0092] A PEO coated Li6 PS 5 Composite solid electrolyte PEO@LiCl 6 PS 5 The preparation method of Cl comprises the following steps:
[0093] Weigh LiNi according to the mass ratio of 8:1:1 0.8 Co 0.1 Mn 0.1 O 2 (LNO-NCM811), Li 6 PS 5 Cl, VGCF (carbon fiber) conductive carbon, NMP (N-methylpyrrolidone) as solvent, mixed and ground for 10 minutes and then coated on aluminum foil. 0.8 Co 0.1 Mn 0.1 O 2 ) loading is 15 mg / cm 2 Around, a composite positive electrode is obtained;
[0094] With the composite cathode as the substrate, PEO and LiTFSI are mixed at a molar ratio of 30:1, dissolved in toluene, and a polymer solution is obtained. The solution is sprayed out from the liquid nozzle of the 3D printing device in a mist form and printed. The toluene solvent is removed by a dryer connected under the nozzle. The diameter of the fibrous polymer is controlled to be about 5 μm, and the width of the grid is about 20 μm. A grid-like PEO layer is obtained. The substrate of the PEO layer is the composite cathode, and the liquid nozzle stops printing.
[0095] Sulfide Li 6 PS 5 Cl is ejected from the powder nozzle of the 3D printing device and printed in the grid of the PEO layer. The polymer solution is mixed with Li 6 PS 5 Cl was printed alternately layer by layer in a pulse printing manner, and the printed grid area was 3×3cm 2 After an interval of 5 seconds, the powder nozzle starts printing powder, and the printing is repeated for 20 layers to obtain a printed composite. The composite is then rolled in a roller press at a speed of 50 cm / min and a pressure of 50 MPa to obtain a polymer-coated sulfide composite solid electrolyte PEO@Li 6 PS 5 Cl, and the composite solid electrolyte PEO@Li 6 PS 5 The ionic conductivity of Cl is 2.2×10 -3 S / cm.
[0096] Using 20μm Li metal foil as the negative electrode, the all-solid-state battery was assembled by roller pressing at a pressure of 50MPa and the electrochemical performance was tested.
[0097] Comparative Example 3
[0098] Direct in-situ solvent mixing and drying to prepare PEO / Li 6 PS 5 Cl (control group) sulfide solid electrolyte (i.e., in comparative example 3, pulse printing is not used, but equal amounts of PEO, Li 6 PS 5 Cl and solvent were mixed and coated on the surface of the composite positive electrode), 20μm Li metal foil was used as the negative electrode, and the all-solid-state battery was assembled by roller pressing at a pressure of 50MPa and the electrochemical performance was tested.
[0099] The electrochemical performance test conditions of Example 3 and Comparative Example 3 are: current 0.3C rate, voltage range 3.0~4.3V (vs.Li + / Li), cycled 500 times, and the test comparison results are shown in Table 3.
[0100] Table 3
[0101]
[0102] It can be seen from Table 3 that the ionic conductivity of the composite solid electrolyte prepared by 3D pulse printing in Example 3 is higher than that in Comparative Example 3, and the 100-cycle capacity retention rate is as high as 95%.
[0103] Example 4: Preparation of composite solid electrolyte
[0104] A Succinonitrile (SN)-coated Li 6 PS 5 Composite solid electrolyte SN@LiCl 6 PS 5 The preparation method of Cl comprises the following steps:
[0105] Weigh LiNi according to the mass ratio of 8:1:1 0.6 Co 0.2 Mn 0.2 O 2 (LNO-NCM622), Li 6 PS 5 Cl, VGCF (carbon fiber) conductive carbon, NMP (N-methylpyrrolidone) as solvent, mixed and ground for 10 minutes and then coated on aluminum foil. 0.6 Co 0.2 Mn 0.2 O 2 ) loading is 15 mg / cm 2 Around, a composite positive electrode is obtained;
[0106] With the composite cathode as the substrate, SN and LiTFSI were mixed at a molar ratio of 30:1, dissolved in toluene, and a polymer solution was obtained. The solution was sprayed out from the liquid nozzle of the 3D printing device in a mist form and printed. The toluene solvent was removed by a dryer connected under the nozzle. The diameter of the fibrous polymer was controlled to be about 5 μm, and the width of the grid was about 20 μm. A grid-like SN layer was obtained. The substrate of the SN layer was the composite cathode, and the liquid nozzle stopped printing.
[0107] Sulfide Li 6 PS 5 Cl is ejected from the powder nozzle of the 3D printing device and printed in the grid of the SN layer. The polymer solution is mixed with Li 6 PS 5 Cl was printed alternately layer by layer in a pulse printing manner, and the printed grid area was 3×3cm 2 After an interval of 5 seconds, the powder nozzle starts printing powder, and the printing is repeated for 20 layers to obtain a printed composite. The composite is then rolled in a roller press at a speed of 50 cm / min and a pressure of 50 MPa to obtain a polymer-coated sulfide composite solid electrolyte SN@Li 6 PS 5 Cl, and the composite solid electrolyte SN@Li 6 PS 5 The ionic conductivity of Cl is 2.5×10 -3 S / cm.
[0108] Using 20μm Li metal foil as the negative electrode, the all-solid-state battery was assembled by roller pressing at a pressure of 50MPa and the electrochemical performance was tested.
[0109] Comparative Example 4
[0110] Direct in-situ preparation of SN / Li by solvent mixing and drying 6 PS 5 Cl (control group) sulfide solid electrolyte (i.e., in comparative example 4, pulse printing is not used, but equal amounts of SN, Li 6 PS 5 Cl and solvent were mixed and coated on the surface of the composite positive electrode), 20μm Li metal foil was used as the negative electrode, and the all-solid-state battery was assembled by roller pressing at a pressure of 50MPa and the electrochemical performance was tested.
[0111] The electrochemical performance test conditions of Example 4 and Comparative Example 4 are: current 0.3C rate, voltage range 3.0~4.3V (vs.Li + / Li), cycled 500 times, and the test comparison results are shown in Table 4.
[0112] Table 4
[0113]
[0114] It can be seen from Table 4 that the ionic conductivity of the composite solid electrolyte prepared by 3D pulse printing in Example 4 is higher than that in Comparative Example 4, and the 100-cycle capacity retention rate is as high as 96%.
[0115] Example 5: Preparation of composite solid electrolyte
[0116] A polyacrylonitrile (PAN) coated Li 6 PS 5 Composite solid electrolyte PAN@LiCl 6 PS 5 The preparation method of Cl comprises the following steps:
[0117] Weigh LiNi according to the mass ratio of 8:1:1 0.8 Co 0.1 Mn 0.1 O 2 (LNO-NCM811), Li 6 PS 5 Cl, VGCF (carbon fiber) conductive carbon, NMP (N-methylpyrrolidone) as solvent, mixed and ground for 10 minutes and then coated on aluminum foil. 0.8 Co 0.1 Mn 0.1 O 2 ) loading is 15 mg / cm 2 Around, a composite positive electrode is obtained;
[0118] With the composite cathode as the substrate, PAN and LiTFSI are mixed in a molar ratio of 30:1, dissolved in toluene, and a polymer solution is obtained. The solution is sprayed out from the liquid nozzle of the 3D printing device in a mist form and printed. The toluene solvent is removed by a dryer connected under the nozzle. The diameter of the fibrous polymer is controlled to be about 5 μm, and the width of the grid is about 20 μm. A grid-like PAN layer is obtained. The substrate of the PAN layer is the composite cathode, and the liquid nozzle suspends printing;
[0119] Sulfide Li 6 PS 5 Cl is ejected from the powder nozzle of the 3D printing device and printed in the grid of the PAN layer. The polymer solution is mixed with Li 6 PS 5 Cl was printed alternately layer by layer in a pulse printing manner, and the printed grid area was 3×3cm 2 After an interval of 5 seconds, the powder nozzle starts printing powder, and the printing is repeated for 20 layers to obtain a printed composite. The composite is then rolled in a roller press at a speed of 50 cm / min and a pressure of 50 MPa to obtain a polymer-coated sulfide composite solid electrolyte PAN@Li6 PS 5 Cl, and the composite solid electrolyte PAN@Li 6 PS 5 The ionic conductivity of Cl is 2.7×10 -3 S / cm.
[0120] Using 20μm Li metal foil as the negative electrode, the all-solid-state battery was assembled by roller pressing at a pressure of 50MPa and the electrochemical performance was tested.
[0121] Comparative Example 5
[0122] Direct in-situ solvent mixing and drying to prepare PAN / Li 6 PS 5 Cl (control group) sulfide solid electrolyte (i.e., in comparative example 5, pulse printing is not used, but equal amounts of PAN, Li 6 PS 5 Cl and solvent were mixed and coated on the surface of the composite positive electrode), 20μm Li metal foil was used as the negative electrode, and the all-solid-state battery was assembled by roller pressing at a pressure of 50MPa and the electrochemical performance was tested.
[0123] The electrochemical performance test conditions of Example 5 and Comparative Example 5 are: current 0.3C rate, voltage range 3.0~4.3V (vs.Li + / Li), cycled 500 times, and the test comparison results are shown in Table 5.
[0124] Table 5
[0125]
[0126]
[0127] It can be seen from Table 5 that the ionic conductivity of the composite solid electrolyte prepared by 3D pulse printing in Example 5 is higher than that in Comparative Example 5, and the 100-cycle capacity retention rate is as high as 95%.
[0128] It can be seen from Tables 1-5 that the polymer-coated sulfide composite solid electrolyte prepared by the present invention is used in all-solid-state batteries, and the various performances of the batteries are significantly improved. Taking into account the solubility of both the polymer and the lithium salt, an organic solvent is usually required. According to the polarity, organic solvents can be divided into high-polarity solvents, low-polarity solvents and non-polar solvents. High-polarity solvents are usually strong Lewis bases, containing electronegative elements such as N and O with lone pairs of electrons. These elements easily react with electrophilic species in sulfides (such as P 5+) to react. In addition, the S atom in the sulfide may attack the electrophilic C atom in the carbonyl group. Due to the interaction between the sulfide and the polar solvent, a phase with low ionic conductivity is generated. Therefore, when preparing a composite solid electrolyte of polymer-coated sulfide, a non-polar or less polar solvent should be selected as much as possible, or the polar solvent should be removed before adding the sulfide. The above example uses the 3D pulse printing method to avoid the interaction between the sulfide and the solvent and the generation of a low ionic conductivity phase.
[0129] It should be understood that the present invention is not limited to the above-mentioned embodiments. For ordinary technicians in this field, improvements or changes can be made based on the above description. Without paying any creative work, all these improvements and changes should fall within the scope of protection of the present invention.
Claims
1. A method for preparing a composite solid electrolyte, characterized in that: The following steps are involved: Passing the polymer solution into a liquid nozzle of a 3D printing device; Passing sulfide into a powder nozzle of a 3D printing device; Spraying the polymer solution onto the electrode through a liquid nozzle of a 3D printing device to form a grid-shaped polymer film; Dispersing the sulfide into the gaps of the polymer film through a powder nozzle of a 3D printing device; The polymer film and the sulfide are printed layer by layer in a pulse printing manner; Rolling to obtain the composite solid electrolyte; Before passing the polymer solution into the liquid nozzle of the 3D printing device, the polymer solution is mixed with the lithium salt; When the sulfide is Li3PS4, the polymer in the polymer solution is polytetrafluoroethylene; When the sulfide is Li6PS5Cl, the polymer in the polymer solution is polyacrylonitrile.
2. The preparation method according to claim 1, characterized in that: The process conditions of the rolling are as follows: the rolling is carried out under the conditions of 5-300 MPa, and the speed of the rolling is 10-80 cm / min.
3. A composite solid electrolyte, characterized in that: The composite solid electrolyte is prepared by the preparation method according to any one of claims 1 to 2, and the mass of the polymer accounts for 1.5% to 49.5% of the total weight of the composite solid electrolyte.
4. The composite solid electrolyte according to claim 3, characterized in that: The mass of the sulfide accounts for 50-98% of the total weight of the composite solid electrolyte; and / or the mass of the lithium salt accounts for 0.001-5% of the total weight of the composite solid electrolyte.
5. The composite solid electrolyte according to claim 3, characterized in that: The composite solid electrolyte is in the form of a thin film.
6. The composite solid electrolyte according to claim 3, characterized in that: The thickness of the composite solid electrolyte is 0.05-3 mm.
7. A lithium ion battery, characterized in that: Comprising the composite solid electrolyte as claimed in claim 3.
Citation Information
Patent Citations
High-flexibility sulfide composite solid electrolyte and preparation method thereof
CN112909332A
Fabric-reinforced ultrathin sulfide electrolyte sheet as well as preparation method and application thereof
CN112909343A